Phage therapy is effective against infection by Mycobacterium ulcerans in a murine footpad model. - Gabriela Trigo; Teresa G Martins; Alexandra G Fraga; Adhemar Longatto-Filho; António G Castro; Joana Azeredo; Jorge Pedrosa (Public Library of Science (PLoS), 2013)
BACKGROUND: Buruli Ulcer (BU) is a neglected, necrotizing skin disease caused by Mycobacterium ulcerans. Currently, there is no vaccine against M. ulcerans infection. Although the World Health Organization recommends a combination of rifampicin and streptomycin for the treatment of BU, clinical management of advanced stages is still based on the surgical resection of infected skin. The use of bacteriophages for the control of bacterial infections has been considered as an alternative or to be used in association with antibiotherapy. Additionally, the mycobacteriophage D29 has previously been shown to display lytic activity against M. ulcerans isolates. METHODOLOGY/PRINCIPAL FINDINGS: We used the mouse footpad model of M. ulcerans infection to evaluate the therapeutic efficacy of treatment with mycobacteriophage D29. Analyses of macroscopic lesions, bacterial burdens, histology and cytokine production were performed in both M. ulcerans-infected footpads and draining lymph nodes (DLN). We have demonstrated that a single subcutaneous injection of the mycobacteriophage D29, administered 33 days after bacterial challenge, was sufficient to decrease pathology and to prevent ulceration. This protection resulted in a significant reduction of M. ulcerans numbers accompanied by an increase of cytokine levels (including IFN-γ), both in footpads and DLN. Additionally, mycobacteriophage D29 treatment induced a cellular infiltrate of a lymphocytic/macrophagic profile. CONCLUSIONS/SIGNIFICANCE: Our observations demonstrate the potential of phage therapy against M. ulcerans infection, paving the way for future studies aiming at the development of novel phage-related therapeutic approaches against BU.